The effect of cryogenic treatment on a high Co bearing DIN 1.2888 steel used as die in hot forging process - Kiraz, Caner; Birol, Burak; Sagin, Ahmet (IOP Publishing Ltd, 2024)
Die steels used in metal forming processes require resilience in harsh conditions. Therefore, it becomes crucial to convert retained austenite into martensite and uniformly distribute fine carbide phases in these steels. Cobalt is known for its ability to enhance carbide formation in tool steels. In the present work, DIN 1.2888, a hot work tool steel characterized by high cobalt content, was subjected to the conventional HT and CT processes at -100, -140, and -180 degrees C for 6 h, then double-tempered. The properties of samples were investigated by XRD, SEM-EDS, and Microhardness analyses. The wear mechanism was investigated by a pin-on-disc wear testing device and the impact toughness of the samples was examined both at room temperature and the working temperature of the dies (350 degrees C). It was observed that decrease of the cryogenic treatment temperature resulted with a slight change on the hardness values of the samples from 507 HV to 529 HV, while impact toughness increased from 12.35 J to 23.44 J at 350 degrees C. Also, the wear rates of the samples exhibited a similar to 50% decrease. It can be deduced that cryogenic treatment had positive effect on the properties of steel, depending on the retained austenite decrement and homogenous fine carbide density increment with the decreasing cryogenic treatment temperature.
Keywords: cryogenic treatment; DIN 1.2888 steel; carbide distribution; mechanical properties; wear; MECHANICAL-PROPERTIES; WEAR BEHAVIOR; TRIBOLOGICAL BEHAVIOR; TOOL STEEL; CARBIDE PRECIPITATION; DEEP; MICROSTRUCTURE; RESISTANCE; TEMPERATURE; EVOLUTION; Materials Science